2012
DOI: 10.3109/14767058.2012.717998
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of oxidant/antioxidant system in newborns and their breast milks

Abstract: In preterm newborns and term SGA infants, total oxidant stress is increased and antioxidant capacity is low. No significant difference was found between mother milks of preterm and term AGA and SGA infants.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
17
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 16 publications
(17 citation statements)
references
References 27 publications
0
17
0
Order By: Relevance
“…Sandal et al reported similar TAC, TOS, and OSI in colostrum of healthy term and preterm newborns. 28 However, in their study, preterm infant group has a high mean gestational age and their results may not be representative for smaller and more vulnerable infants. Two studies with small sample sizes showed similar antioxidant levels in preterm and healthy term BM.…”
Section: Discussionmentioning
confidence: 87%
“…Sandal et al reported similar TAC, TOS, and OSI in colostrum of healthy term and preterm newborns. 28 However, in their study, preterm infant group has a high mean gestational age and their results may not be representative for smaller and more vulnerable infants. Two studies with small sample sizes showed similar antioxidant levels in preterm and healthy term BM.…”
Section: Discussionmentioning
confidence: 87%
“…Preterm infants are born relatively deficient in antioxidant defenses, with increased oxidant stress [5]. Many events, such as infection, mechanical ventilation, intravenous nutrition, and blood transfusions result in oxidative stress.…”
Section: Discussionmentioning
confidence: 99%
“…The premature infant is especially susceptible to damage from oxidative stress for two reasons: (1) adequate concentrations of antioxidants may be absent at birth; (2) the ability to increase synthesis of antioxidants is impaired. This can lead to an increased risk for the development of oxidative stress–induced diseases such as bronchopulmonary dysplasia (BPD), retinopathy of prematurity (ROP), necrotizing enterocolitis (NEC), and periventricular leukomalacia (PVL) [5,6]. Therefore, it is critical in premature infants to ensure an adequate supply of dietary antioxidants.…”
Section: Introductionmentioning
confidence: 99%
“…These tests include superoxide, hydrogen peroxide, hydroxyl, single oxygen and peroxynitrite scavenging assays. However, TAS determination may give more precise information than the measurement of each component separately, since the decrease in one component may be compensated by the increase in another, so that all the antioxidant machinery behaves as a self-regulating system (Sandal et al, 2013).…”
Section: Determination Of Total Antioxidant Capacity In Human Milkmentioning
confidence: 99%
“…The child's exposure to the environment outside the womb is an oxidative challenge, and requires an adaptation from a low-oxygen to a high-oxygen environment. This high oxygen concentration increases aerobic metabolic pathways and causes toxic effects on tissues, pathologic cellular changes and increase in free radical products (Gitto et al, 2012;Sandal et al, 2013;Mutinati et al, 2014).…”
Section: Introductionmentioning
confidence: 99%